2015
DOI: 10.2217/epi.15.20
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Butyrate, A Histone Deacetylase Inhibitor in Diabetes Mellitus: Experimental Evidence for Therapeutic Intervention

Abstract: The contribution of epigenetic mechanisms in diabetes mellitus (DM), β-cell reprogramming and its complications is an emerging concept. Recent evidence suggests that there is a link between DM and histone deacetylases (HDACs), because HDAC inhibitors promote β-cell differentiation, proliferation, function and improve insulin resistance. Moreover, gut microbes and diet-derived products can alter the host epigenome. Furthermore, butyrate and butyrate-producing microbes are decreased in DM. Butyrate is a short-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 92 publications
(123 reference statements)
1
39
0
1
Order By: Relevance
“…Tolhurst et al demonstrated that short fatty acids stimulate the secretion of GLP-1 in vitro [34]. Also, some suggest that there is a relationship between the short fatty acid as histone deacetylases inhibitors and the role of epigenetics in the development of diabetes [35]. It has to be emphasized that, in recent studies, it is reported that the amount of butyrate producers such as Roseburia species and Faecalibacterium prausnitzii is lower in patients affected with T2DM [11, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Tolhurst et al demonstrated that short fatty acids stimulate the secretion of GLP-1 in vitro [34]. Also, some suggest that there is a relationship between the short fatty acid as histone deacetylases inhibitors and the role of epigenetics in the development of diabetes [35]. It has to be emphasized that, in recent studies, it is reported that the amount of butyrate producers such as Roseburia species and Faecalibacterium prausnitzii is lower in patients affected with T2DM [11, 36].…”
Section: Discussionmentioning
confidence: 99%
“…The SCFA butyric acid (i.e. butyrate), in particular, is used as energy by colonocytes to maintain the mucosal barrier [15,21,22] and can regulate the expression of genes related to glucose metabolism [23]. Higher concentrations of butyrate and other SCFAs in the stool, however, may indicate that these metabolites are being excreted rather than absorbed [24].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, histone deacetylases and histone acetyltransferases are among the most important components in the modulation of pathological conditions in both diabetes and heart failure [Olson et al, ; Khan and Jena, ]. Histone acetyltransferase (HAT) and histone deacetylase (HDAC) have emerged as crucial factors in the developing process of cardiac disorders with diverse etiologies [Sun et al, ; Kurdi and Booz, ].…”
mentioning
confidence: 99%